The role of nursing in enhancing quality of life for lung cancer patients receiving targeted and immunotherapy: Challenges, opportunities, and future directions - Ying-Ying Sun; Li-Min Wei; Ying Qian (Human Vaccines & Immunotherapeutics)
Targeted therapy and immunotherapy are two critical contemporary strategies in the management of lung cancer. Despite their success in extending survival and mitigating symptoms, they introduce complex nursing interventions. This narrative review examines the impact of these treatment strategies on patients’ quality of life, assesses the efficacy of current nursing interventions, and proposes strategies for enhancing future nursing practices. A comprehensive analysis of existing literature, covering studies published between 2014 and 2024 in the databases of WOSCC- SCIE, PubMed, CINAHL, and Embase, underscores the pivotal role of nursing in managing treatment-related adverse effects, delivering psychosocial support, and educating patients. Nevertheless, challenges remain in the areas of nursing staff training, resource allocation, and the limited scope of nursing research. Future directions should focus on the development of individualized care plans, the integration of innovative nursing technologies, and the ongoing enhancement of care quality to optimize nursing practices.